New records of two hyphomycetous fungi Monodictys putredinis (Wallr.) Hughes and Stachybotrys atra Corda for Bangladesh - Shamsi, Shamim; Sultana, Razia (Bangladesh Journal of Plant Taxonomy, 2010)
Not available. Keywords: Monodictys putredinis; new records; Stachybotrys atra. DOI: 10.3329/bjpt.v17i1.5397 <span style="font-family: "Times New Roman"; font-size: 9pt; mso-fareast-font-family: "Times New Roman"; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-bidi-font-family: "Times New Roman"; mso-bidi-font-size: 12.0pt;">Bangladesh<span style="font-family: "Times New Roman"; font-size: 9pt; mso-fareast-font-family: "Times New Roman"; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-bidi-font-family: "Times New Roman"; mso-bidi-font-size: 12.0pt;"> J. Plant Taxon. 17(1): 101-103, 2010 (June)